2008
DOI: 10.1080/15435070802414447
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring an Electrode Flooding Through the Back Pressure in a Proton Exchange Membrane (PEM) Fuel Cell

Abstract: For proton exchange membrane (PEM) fuel cells, proper water management is important to obtain maximum performance. In understanding the water process within the fuel cell, the exhaust back pressure was found to be a useful indicator of the water content within the cell. Measured back pressure at the exhaust is an indication of how much water content is in the membrane during the electrochemical reaction. From these experiments, the measured back pressure shows when the fuel cell suffered from flooding because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Proton exchange membrane fuel cell (PEMFC) has high energy efficiency, zero emission, and rapid startup capability, making it a desirable clean power source for stationary, mobile, and portable applications. One of the critical issues in PEMFC is the water management because a delicate water balance is required to obtain a good cell performance and durability . Water accumulates in the cathode due to reaction and electroosmotic drag effect and is mainly removed by gas flow in the cathode gas flow channel; a good water management strategy in PEMFC hence requires the understanding of water behavior in the gas flow channel.…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) has high energy efficiency, zero emission, and rapid startup capability, making it a desirable clean power source for stationary, mobile, and portable applications. One of the critical issues in PEMFC is the water management because a delicate water balance is required to obtain a good cell performance and durability . Water accumulates in the cathode due to reaction and electroosmotic drag effect and is mainly removed by gas flow in the cathode gas flow channel; a good water management strategy in PEMFC hence requires the understanding of water behavior in the gas flow channel.…”
Section: Introductionmentioning
confidence: 99%
“…Y. H. Park and J. A. Caton found that the outlet back pressure is a useful indicator of the water content and relative humidity inside the PEMFC . With relative humidity of 100% at both anode and cathode side will result in flooding which decreases the performance of PEMFC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, liquid water is one of the key factors responsible for the degradation of electrolyte membrane. Because Springer et al [9] and Bernardi and Verbrugge [10] developed a one-dimensional PEM fuel cell model including various modes of water transport, numerous research works have been focused on the analysis of water transport and management [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Most of them addressed liquid water transport in the electrolyte membrane and GDL.…”
Section: Introductionmentioning
confidence: 99%